The Effect of Gender, Socio-Economic Status, and Using Mindmaple Lite Software on Learners’ Writing Performance - Sabarun, Sabarun (Language Circle: Journal of Language and Literature, 2022)
The research was to measure interaction effects for gender, socio-economic status, and using MindMaple lite Software toward writing skills. The investigation used a quasi-experiment design using test as instrument. The subjects were 36 learners at Islamic higher education in Central Kalimantan consisting of 17 males and 19 females; 11 high, 10 middle, and 15 low learners; 17 using MindMaple, and 19 without using MindMaple. A three-way analysis of variance test was applied to perform data analysis. The finding indicated that a different effect occurred for gender (F=8.780; p=0.007); socio economic status (F=4.421; p=0.023), writing strategy using MindMaple (F=36.023; p=0.000) on writing performance. The study indicated an interaction effect occured between gender and socio-economic (F=6.927, p=0.004). Here, females performed better than males; high socio-economic learners did better than the others; learners using MindMaple ware performed better than without using MindMaple. In contrast, the finding found that interaction effect did not occur between gender and writing strategy (F=1.135, p=0.297); socio-economic and writing strategy (F=0.198, p=0.822); gender, socio-economic and writing strategy using MindMaple (F=0.437, p=0.651).  The study concluded that gender, socio-economic and writing strategy did not give significant contribution simultaneously on writing performance. It gave new insights on the implementation of MindMaple in L2 writing class.